Anàlise de textos multimodais da web e o ISD - Ferreira, Anise D'Orange [UNESP]; De Melo, Glenda Cristina Valim (FapUNIFESP (SciELO), 2016)
In this article we present, firstly, the compatibility between the analysis from the Socio-discursive Interactionism (SDI) proposed by Bronckart (1999, 2006, 2008) and the multimodal texts from Baldry & Thibault (2010). Both of them share similarities concerning the social view of the language, genre and analysis levels. Secondly, it is also intended to show that the differences among the analytical instruments do not interfere in the appropriation of analytical elements of web multimodal texts and the SDI analytical plan. Concomitantly, we exemplify the purpose through a web text analysis.
WEB multimodal text analysis and SID
Keywords: Data analysis; Socio-discursive interactionism; The multimodal texts